The influence of the quality and safety of food products on the health and well-being of the population - Kotelevych, V.; Huralska, S.; Hоncharenko, V. (Scientific Progress & Innovations, 2023)
The quality and safety of food products is a global problem, the solution of which requires the consolidation of efforts at the world, national and regional levels. For Ukraine, food security has become particularly acute: environmental pollution with radioactive substances as a result of the accident at the Chernobyl nuclear power plant and other harmful substances of man-made origin, war, lack of high-quality and nutritious food for the population. the majority of the population; all this has a negative effect on health, life expectancy and working capacity. The purpose of our research was to analyze the publications of scientists and highlight the current problems of quality and safety of food products in the context of ensuring food safety and the health and well-being of the population. It was established that the state of the ecological situation in Ukraine has significantly worsened and the scale of environmental pollution with harmful substances has increased several times over the last decade, which enter the human body along the chain: soil - plants - animals - food. Therefore, food products and the conditions and means of their production are the main sources of risks and the object of special attention of scientists and consumers. It has been established that more than 70% of harmful substances enter the human body with food products that pose a threat to health, slowly destroying it, laying the causes of future disorders and diseases. Food adulteration is a global threat. The result of the negative impact of these dangers is the loss of health, a decrease in life expectancy, an increase in mortality due to food poisoning, and a deterioration of the diet due to low-quality products. Many current health issues are related to the activation and integration of food production, the growing contact between humans and animals. Excessive use of antibiotics in animal husbandry has caused the global problem of antibiotic resistance of microorganisms. Food products are one of the ways of formation of antibiotic-resistant strains of bacteria. Bacteria are able to easily exchange genetic information in the environment, which makes it possible to transfer different mechanisms of resistance from one to another. Therefore, the health of people is connected with the health of animals and the hygiene of the environment, which determines the need for close cooperation between doctors of humane and veterinary medicine and specialists in environmental hygiene